The Effectiveness of Bilingual Instruction in Student Learning: A Literature Review - Nur Afifah, Laila (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2005)
Bilingual instruction has gained increasing attention in multilingual educational contexts, particularly in primary education where students are still developing foundational language and cognitive skills. Language plays a crucial role in shaping students’ comprehension, participation, and learning outcomes, especially in subjects that require conceptual understanding such as mathematics. In Indonesia and other multilingual settings, the coexistence of a national language and multiple regional languages presents both opportunities and challenges for classroom instruction, making bilingual approaches a relevant pedagogical strategy. This study aims to synthesize existing research on the effectiveness of bilingual instruction in student learning, with a particular focus on primary mathematics education. A literature review methodology was employed by analyzing peer-reviewed journal articles and scholarly books published between 2015 and 2024. The selected literature was examined using a descriptive qualitative synthesis to identify dominant themes, methodological trends, and reported outcomes related to bilingual instructional practices. The findings indicate that bilingual instruction consistently supports students’ conceptual understanding, classroom participation, and learning confidence. The use of the mother tongue alongside the national language reduces linguistic barriers, facilitates comprehension of abstract concepts, and promotes more inclusive learning environments. Overall, the reviewed literature suggests that bilingual instruction is an effective pedagogical approach in multilingual primary education contexts.